Reactive Attachment Disorder (RAD) in children living in a special childcare centres - Kołodziejczak, Liliana (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
The article will widely discuss Reactive Disorders ties with pupils care and educational institution, their causes, diagnostic criteria and symptoms.
Keywords: Reactive Attachment Disorder; types of attachment; special educational centre; children rejected